The Impact of Netizen Responses (Public) on Social Media on the Mental Health of Volleyball Athletes in Garut Regency - Khansa Sri Santika; Asma Bara; Alam Hadi Kosasih (Universitas Hamzanwadi, 2026)
Exposure to netizen comments on social media has the potential to affect athletes’ mental health; however, research on its impact on district-level volleyball players remains limited. This study aims to examine the relationship between and the influence of netizen comments on depression, anxiety, and stress among volleyball players in Garut District. A quantitative correlational method using a survey was employed. A total of 27 active volleyball athletes were selected using purposive sampling based on the criteria of regularly accessing social media at least 3 times per week and having received public comments within the last 3 months. The instruments included a netizen response questionnaire and the DASS-21, which have been validated for both validity and reliability (Cronbach’s Alpha > 0.70). Data analysis utilized descriptive statistics, Spearman’s correlation test, and path analysis. The results indicated that anxiety had the highest mean score (15.63), with 33.3% of athletes falling into the very severe category. There was a significant positive relationship between netizen responses and depression (rₛ=0.476), anxiety (rₛ=0.631), and stress (rₛ=0.559). Path analysis confirmed the significant influence of netizen responses on athletes’ mental health (β=0.658; R²=0.433). The conclusion of this study is that netizen responses are an important psychosocial factor influencing athletes’ mental health, particularly anxiety.